Informing future research for carriage of multiresistant Gram-negative bacteria: problems with recruiting to an English stool sample community prevalence study. Issue 12 (10th December 2017) - Lecky, Donna M; Nakiboneka-Ssenabulya, Deborah; Nichols, Tom; Hawkey, Peter; Turner, Kim; Chung, Keun-Taik; Thomas, Mike; Thomas, Helen Lucy; Xu McCrae, Li; Shabir, Sahida; Manzoor, Susan; Alvarez-Buylla, Adela; et al.
Abstract : Objectives: This study aims to highlight problems with recruiting to an English stool sample community prevalence study. It was part of a larger cross-sectional research to determine the risk factors for the presence of extended-spectrum beta-lactamase and carbapenemase-producing coliforms in stool samples of the asymptomatic general English population. Setting: Four National Health Service primary care trusts (PCTs) of England representing a different section of the population of England: Newham PCT; Heart of Birmingham Teaching PCT; Shropshire County PCT; and Southampton City PCT. Participants: Sixteen general practices across the four PCTs were purposefully selected. After stratification of GP lists by age, ethnicity and antibiotic use, 58 337 randomly selected patients were sent a postal invitation. Patients who had died, moved to a different surgery, were deemed too ill by their General Practitioner or hospitalised at the time of mailing were excluded. Results: Stool and questionnaire returns varied by area, age, gender and ethnicity; the highest return rate of 27.3% was in Shropshire in the age group of over 60 years; the lowest, 0.6%, was in Birmingham in the age group of 18–39 years. Whereas only 3.9%(2296) returned a completed questionnaire and stool sample, 94.9% of participants gave permission for their sample and data to be used in future research. Conclusion: Researchers should consider the low stool specimen return rate and wide variation by ethnicity and age when planning future studies involving stool specimen collection. This is particularly pertinent if the study has no health benefit to participants. Further research is needed to explore how to improve recruitment in multicultural communities and in younger people.